PERAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA DI SMPN 9 BATAM - Aniza Juanti; M. Imamuddin; Eny Murtiyastuti; Roland Marudut Halomaun Simatupang (Universitas Pahlawan Tuanku Tambusai, 2022)
The teacher is a teacher who has provision in knowledge. The teacher as a motivator who provides direction, views, and enthusiasm in learning activities. Apart from that math lessons are mind draining which can make you bored, you really need motivation and direction. And the role of the teacher in the learning and teaching process includes [1] The teacher as education. [2] Teachers as instructors. [3] Teachers as learning resources. [4] The teacher as a facilitator. [5] Teachers as administrators. [6] Teacher as movement. [7] The teacher as a motivator. This study aims to find out how the role of a teacher in increasing motivation to learn mathematics at SMPN 9 Batam. This type of research is descriptive. The subjects used in this study were curriculum assistant teachers, mathematics teachers, and several class IX.10 students at SMPN 9 Batam. The data collection techniques used were observation and interviews related to the teacher's role in increasing motivation to learn mathematics which consists of 6 indicators, namely [1] There is a desire or desire to succeed. [2] There is an urge and need in learning. [3] There is a hope and aspiration to face the future. [4] There is appreciation in learning. [5] There is an interesting activity in learning. [6] There is a more conducive learning environment that allows students to learn better. The results of this study are that in the application of classroom learning a teacher must have things that support according to the indicators of current learning motivation which are said with things that support, namely [1] Ideas, a teacher must have ideas, namely thinking and creativity. [2] Analysis, teachers must be able to analyze and be able to see the strengths and weaknesses that occur in class during the mathematics learning process. [3] Media, basically the learning process requires media both written, audio and even visual media. [4] Layout, where the teacher can organize a room that can have a positive impact on the learning that will be applied. [5] Class activities, activities that occur can be arranged by the teacher both in conceptualizing learning and can give an overview of local activities. [6] Evaluation, evaluation can be feedback to the teacher to be able to develop learning that will be applied in the next meeting. Keywords:The role of the teacher, learning motivation